(Tissue PET) Vascular metabolic imaging and peripheral plasma biomarkers in the evolution of chronic aortic dissections. (14th January 2015) - Sakalihasan, Natzi; Nienaber, Christoph A.; Hustinx, Roland; Lovinfosse, Pierre; El Hachemi, Mounia; Cheramy-Bien, Jean-Paul; Seidel, Laurence; Lavigne, Jean-Paul; Quaniers, Janine; Kerstenne, Marie-Ange; Courtois, Audrey; Ooms, Annie; et al.
Abstract: Aims: Despite adequate medical management, dissection of the descending aorta (type B) may develop complications, including aneurysmal progression and eventually rupture. Partial false lumen thrombosis has been identified as a marker of adverse evolution in chronic dissection. The aim of this study was to test the ability of complementary information, provided by 18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography/computed tomography (PET/CT) and peripheral biomarkers, to add pathophysiological significance and a prognostic value to morphological data. Methods and results: We explored serial aortic 18 F-FDG uptake by PET/CT imaging and plasma biomarkers in a series of 23 patients with type B dissection to predict complications from initial data and to investigate potential associations with aneurysmal expansion during follow-up. Complications occurred in 17 patients. Acute initial characteristics associated with complications were male gender ( P = 0.021), arterial hypertension ( P = 0.040), aortic dissection diameter ( P = 0.0086), partial thrombosis of the false channel ( P = 0.0046), and enhanced focal 18 F-FDG uptake ( P = 0.045). During follow-up (mean 16.7 ± 8.0 months), aneurysmal expansion was associated with false lumen morphology ( P < 0.0001), quantitative 18 F-FDG uptake, ( P = 0.0029), elevated plasma concentrations of biomarkers of platelets (P-selectin, P = 0.0009) and thrombin activation (TAT complexes, P = 0.0075), and fibrinolysis (PAP complexes, P < 0.0001; D-dimers, P = 0.0006). Plasma markers of coagulation and fibrinolysis were related to false channel morphology, suggesting that thrombus biological dynamics may drive progressive expansion of type B dissections. Conclusion: Enhanced FDG uptake may be considered as a complementary imaging marker associated with secondary complications in type B dissections. During follow-up, aneurysmal progression is related to PET/CT and biomarkers of thrombus renewal and lysis.